ANALISIS PERSEPSI DAN PERILAKU MASYARAKAT TERHADAP KEPUTUSAN MENGGUNAKAN PRODUK HALAL KOSMETIK WARDAH (STUDI DI KECAMATAN PAMIJAHAN DAN KECAMATAN CIBUNGBULANG BOGOR) - Trisia Amalia; Rully Trihantana; Ermi Suryani (SAHID BUSINESS JOURNAL, 2022)
Considering that the majority of people in Indonesia are Muslim, and it is an obligation, especially for the Muslim community, to always use Halal products, especially Halal cosmetic products. With the circulation of various kinds of Halal cosmetics in the community, behavior and perceptions arise, therefore people need to choose and be careful in using Halal cosmetic brands. The purpose of this study was to analyze the perception and behavior of the people of Pamijahan and Cibungbulang sub-districts towards the decision to use Wardah cosmetic Halal products. This type of research uses quantitative research that uses a Likert scale, with a sample of 100 respondents. The technique used in taking the research sample is the purposive sampling technique and using the Yamane formula. The analytical method used is Multiple Linear Regression Analysis and using IBM SPSS Version 25 software. The results showed partially the perception variable had a positive effect on the decision to use, with a tcount value of 2,219 > ttable 1,993. Meanwhile, behavior has a positive effect on the decision to use, with a tcount of 2,968 > ttable of 1,993. And simultaneously the behavior and perceptions of society have a positive effect on the decision to use. This is evidenced by the calculated F value of 15,469 > 3.97.